SPECIFICS OF LEFT VENTRICLE REMODELLING IN CHILDREN WHO HAVE HAD DIPHTHERITIC CARDITIS - U.K. Gadzhieva (Педиатрическая фармакология)
Carditis has a special place among diphtheritic complications determining a disease prognosis. The article provides results of studying a functional status of cardiac muscle in children who have had diphtheritic complications in the short-term (2–3 years; n = 35) and longterm (9–10 years; n = 15) follow-up. Echo cardiographic test showed there were three hemodynamic options available for diphtheritic carditis development: normal volumetric parameters of the left ventricle cavity; an enlarged left ventricle cavity and reduced myocardial contractility (dilated cardiomyopathy); a reduced left ventricle cavity with intact myocardial contractility (diastolic dysfunction). Including vitamin E and Carnitine chloride into the treatment for children who have had Diphtheritic Carditis results in improvements both to the cardiac systolic and diastolic functions.Key words: children, diphtheritic carditis, cardiac remodelling, cardiomyopathy, diastolic function.